2002
DOI: 10.1002/mrd.10222
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of the two GH genes during embryonic development of rainbow trout oncorhynchus mykiss in relation with the IGFs system

Abstract: The Growth hormone (GH)/insulin-like growth factor (IGF) system promotes embryonic growth in higher vertebrates. Such a system exists in salmonids, but exhibits an additional level of complexity resulting from a recent whole genome tetraploidisation. Thus, two nonallelic GH genes are present in the trout genome. Although the two GH genes are similar, the possibility remains that the two genes have evolved separately, acquiring a distinct expression pattern. In this study, using whole mounted in situ hybridisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 39 publications
4
23
0
Order By: Relevance
“…As pepck is transcriptionally regulated by several other hormones in addition to insulin, interpretation of its regulation and its relative response in male and female zebrafish requires careful consideration. The IGF axis genes, igf-1, igf-2 and igfbp-5 were up-regulated in males, suggesting increased mitogenic activity similar to previous results in rainbow trout (Gabillard et al, 2003). It is possible that increased expression of components of the IGF axis in males is associated with protein economy, as one mechanism of IGF is to decrease protein degradation (Hill et al, 1999;Bell and McDermott, 2000).…”
Section: Sexual Dimorphism Of the Hepatic Transcriptomesupporting
confidence: 81%
“…As pepck is transcriptionally regulated by several other hormones in addition to insulin, interpretation of its regulation and its relative response in male and female zebrafish requires careful consideration. The IGF axis genes, igf-1, igf-2 and igfbp-5 were up-regulated in males, suggesting increased mitogenic activity similar to previous results in rainbow trout (Gabillard et al, 2003). It is possible that increased expression of components of the IGF axis in males is associated with protein economy, as one mechanism of IGF is to decrease protein degradation (Hill et al, 1999;Bell and McDermott, 2000).…”
Section: Sexual Dimorphism Of the Hepatic Transcriptomesupporting
confidence: 81%
“…It could be that many of the duplicated genes that have been discovered have significant physiological roles and thus it is advantageous to have redundancy or there could be other reasons why these genes persist. Evolution of novel function is one suggested reason why duplicate genes would persist, but the novelty could be subtle, such as tissue-specific expression (Coon et al 1999) or development stage-specific expression (Gabillard et al 2003) and may not be influenced by the coding sequence itself, but by promoter or regulatory elements upstream of the gene or, in genes such as the POMC gene, in its post-translational processing.…”
Section: Figurementioning
confidence: 99%
“…Quantitative real-time RT-PCR was performed as previously described (Gabillard et al 2003a). Briefly, 1 mg total RNA was used to perform the RT reaction (Applied Biosystems kit no.…”
Section: Trials 4 Andmentioning
confidence: 99%
“…Indeed, in rainbow trout, two GH and IGFR-I genes have been described (Agellon et al 1988, Greene & Chen 1999, Gabillard et al 2003a, while there is no evidence of IGF-I or -II duplicates. Several works have reported a weak differential expression of both GH genes according to the physiological state (Salam et al 1999, Mori et al 2001, Gabillard et al 2003a, while no obvious difference was observed between the two IGFR-I genes (Gabillard et al 2003b(Gabillard et al , 2003c. Recently, the GHR gene was found to be duplicated in salmon (Fukada et al 2004), but the regulation of both GHR genes has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%